Debating Stephen Hawking’s Thought on Creation of Universe: A Qur’anic Scientific Interpretation Perspective - Deki Ridho Adi; Aqdi Rofiq Asnawi; Nur Hidayaturrohmah (AL QUDS : Jurnal Studi Alquran dan Hadis, 2022)
Stephen Hawking’s theory “M” posits that the universe was formed without the assistance of God. This paper elaborates the qur’anic position on Hawking’s idea by analyzing the qur’anic scientific interpretation of universe creation. Therefore, the literature review was utilized to collect as much data as feasible, which was then evaluated using the descriptive-analytical method. The findings of this study indicate that Stephen Hawking’s “M” hypothesis has three faults, which constitute a scientific critique of the interpretation of Qur’anic texts relating to the earth and sky. The three faults are: 1) Earth and sky were not created without God’s intervention, as Hawking claimed, but by the will and strength of Allah. This finding is stated in the interpretation of Surah Al-Anbiya’ verse 30, Al-Fushshilat verse 10, and Al-A’raf verse 54. 2) Hawking’s concept of creation is inappropriate since it is based on the rationalism of liberal thought. The natural creation process described in the Qur’an, scientifically proved by science, differs from Hawking’s claim. 3) Hawking’s idea of a mechanism for creating the heavens and the earth is not suitable with the scientific facts regarding them stated in the Qur’an’s scientific interpretation